Meningkatkan Literasi Digital Mahasiswa melalui Pelatihan Penggunaan ChatGPT Berbasis Artificial Intelligence - Rahmad Akbar; Hayatul Khairul Rahmat; Dzulhijjah Yetti; Nurkholis Nurkholis; Nina Veronika (PT Hakhara Akademia Indonesia, 2025)
The development of Artificial Intelligence (AI) has brought significant changes to higher education, particularly in the way students access, process, and utilize digital information. One rapidly advancing AI technology is ChatGPT, an artificial intelligence–based language model capable of supporting learning processes, academic writing, basic data analysis, and problem solving. However, the use of ChatGPT among students still faces various challenges, such as low levels of critical digital literacy, the potential misuse of technology, and a lack of understanding of academic ethics. This community service activity aims to enhance students’ digital literacy through training on the critical, ethical, and productive use of AI-based ChatGPT. The implementation methods include needs analysis, development of training modules, hands-on practice–based training, and evaluation through pre-tests and post-tests. The results indicate a significant improvement in students’ understanding of AI concepts, their ability to use ChatGPT responsibly, and the enhancement of digital literacy skills in an academic context. This activity is expected to support the strengthening of student competencies in facing digital transformation in higher education.